Yoga on Quality of Life among Women with Breast Cancer Related Lymphoedema (BCRL): A Randomised Control Trial - Minal Panchal; Biman Bihari Paul (Dr. Chinmay Pandya, 2022)
Breast cancer-related lymphoedema (BCRL) is a global healthcare issue that has a significant impact on the emotional and life quality of breast cancer survivors. This study aims to evaluation of the effect of yoga on quality of life and emotional factors in women who have breast cancer related lymphoedema (BCRL). The subjects (women = 40) over the age of 18 from HCG Sola, Civil, and other hospitals in Ahmedabad were divided randomly into two groups; one was the experimental group (n = 20) and the other was the control group (n = 20). An unpaired t-test of all domains of the "LYMQOL ARM Lymphoedema Quality of Life Tool" was performed between the pre-data of the experimental group and the pre-data of the control group. By conventional criteria, this difference was considered to be not statistically significant. The study design was a randomised-control trial. All participants and witnesses signed the consent form. The scale used to measure the lymphoedema quality of life level of the subjects before and after the intervention of both groups was the "LYMQOL ARM Lymphoedema Quality of Life Tool" Scale, The experimental group had an eight-week yoga-based intervention. Sessions were held five days a week. The analyzed data was calculated by the dependent sample (paired) 't'-test. The experimental group's function domain score was statistically significant (p 0.0001), and due to the control group's self-management was similarly significant (p = 0.031). The experimental group's appearance score was statistically significant (p 0.0001), but the control group's was not (p = 0.1256). The experimental group's symptom score was statistically significant (p =0.0265), but the control group's was not (p =0.2371). The experimental group's emotional score was statistically significant (p 0.0001), but the control group's was not significant (p = 0.1041). The experimental group's quality of life score was statistically significant (p 0.0001), but the control group's was not (p = 0.2141). Thus study, supported yogic intervention mediated improvement in quality of life and general wellness for women with breast cancer-related lymphoedema (BCRL).